Thermal evaluation of the modifications in the envelopes of experimental modules located in the community of Imata (4519 masl), Arequipa - Ponce Gonzales, Martín Concepción (2021)
This paper analyzes the different thermal and dynamic energy contributions of the different proposals for modifications made in the envelopes of two experimental housing modules built in the town of Imata, Arequipa at 4519 meters above sea level. The modules were built with constructive characteristics of the place and typical design, later modifications were made such as changing the roof covering material, plastering the adobe walls with plaster, placing skylights on the ceiling and false ceiling, insulation of the false ceiling, and construction of a greenhouse attached to one of the modules. The data recording consisted of measuring the indoor air temperature of the modules and attached greenhouse, in addition to the outdoor meteorological data recording using a Davis station located at the top of the Imata municipality. The average daily indoor air temperature of the module without greenhouse (M1) was initially 3.1 ° C, the average daily outdoor temperature being 0.61 ° C; With the modifications of the envelopes, the average temperature of the interior air of M1 was 10 ° C, contributing an average of 6.9 ° C to the interior; For the module with greenhouse (M2), the mean indoor air temperature was 14.6 ° C, contributing an average of 11.5 ° C indoors with an average difference of 5.17 ° C above M1. The results obtained demonstrate the contribution of the bioclimatic modifications and techniques implemented, such as the case of the attached greenhouse, which are suitable and effective for the High Andean areas due to their solar potential.